2018
DOI: 10.1152/japplphysiol.00394.2018
|View full text |Cite
|
Sign up to set email alerts
|

Lower cutaneous microvascular reactivity in adult cancer patients receiving chemotherapy

Abstract: Cancer patients with a history of anticancer chemotherapy are at an increased cardiovascular disease risk compared with cancer-free populations. Therefore, we tested the hypothesis that cancer patients receiving adjuvant chemotherapy would have a lower cutaneous microvascular reactivity and lower endothelium-dependent flow-mediated dilation (FMD) of the brachial artery compared with matched cancer-free control subjects. To test this hypothesis, we performed a case control study with seven cancer patients recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 67 publications
(109 reference statements)
3
18
0
Order By: Relevance
“…The ACh protocol consisted of a baseline measurement followed by seven current pulses (100-μA anodal current) of 20 s, separated by 60 s current-free intervals. This delivery protocol is consistent with our previous work and has been shown to elicit no detectable current-induced axon-mediated vasodilation [ 14 , 18 ]. To determine endothelium-independent dilation ( part 2 ), 200 μL of a 1% SNP solution was administered.…”
Section: Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…The ACh protocol consisted of a baseline measurement followed by seven current pulses (100-μA anodal current) of 20 s, separated by 60 s current-free intervals. This delivery protocol is consistent with our previous work and has been shown to elicit no detectable current-induced axon-mediated vasodilation [ 14 , 18 ]. To determine endothelium-independent dilation ( part 2 ), 200 μL of a 1% SNP solution was administered.…”
Section: Methodssupporting
confidence: 89%
“…There are several experimental considerations regarding this study. First, some of the patients in the present study also received chemotherapy, which by itself has previously been shown to decrease cutaneous microvascular function [ 14 ]. Since the effects of chemotherapy are systemic and patients served as their own control, this allowed these patients to be included in the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microvascular cutaneous blood flow using laser-Doppler flowmetry (LDF cut ) has often been utilized to non-invasively measure the flux of red blood cells in the skin to assess endothelial function in healthy and clinical populations (Farkas, Kolossvary, Jarai, Nemcsik, & Farsang, 2004;Sutterfield et al, 2018;Verma, Buchanan, & Anderson, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Microvascular cutaneous blood flow using laser‐Doppler flowmetry (LDF cut ) has often been utilized to non‐invasively measure the flux of red blood cells in the skin to assess endothelial function in healthy and clinical populations (Farkas, Kolossvary, Jarai, Nemcsik, & Farsang, ; Sutterfield et al., ; Verma, Buchanan, & Anderson, ). It has been suggested that LDF cut could be utilized as a model to determine dysfunction in the global microvasculature (Holowatz, Thompson‐Torgerson, & Kenney, ).…”
Section: Introductionmentioning
confidence: 99%